Assessing the Use of Scoria and Steel Slag in Purification of Biogas - Linah Kizza (Uganda Christian University, 2025)
The research study determined the composition of biogas produced by medium scale farms in Namulonge, Wakiso district, which were utilizing different feed stocks. Farm 2 (cow dung and poultry) had a higher methane content (53.8%) and low impurities, farm 1 (Cow dung only) exhibited lower methane (49.1%) and high impurities. The adsorption materials, Scoria and Steel slag were tested with varying mix ratios and an optimum mix of 600g Scoria and 600g Steel slag achieved a 69% reduction in carbon dioxide, a complete removal of hydrogen sulfide and a methane increment of 17.3%. A purification unit with a calculated chamber height of 49.7cm was designed and fabricated. The unit was tested across the three farms. Methane increased to 64.2%, 66.3% and 63.3% for farm 1, 2 and 3 respectively while the impurities reduced, having hydrogen sulfide removed completely for all farms. A cost benefit analysis was then carried out for the materials which revealed that scoria and steel slag are more cost efficient compared to Iron oxide pellets, activated carbon, ferric oxide, clay pellets and lime.
Undergraduate